The autophagy pathway participates in resistance to tomato yellow leaf curl virus infection in whiteflies. Issue 9 (1st September 2016) - Wang, Lan-Lan; Wang, Xin-Ru; Wei, Xue-Mei; Huang, Huang; Wu, Jian-Xiang; Chen, Xue-Xin; Liu, Shu-Sheng; Wang, Xiao-Wei
ABSTRACT: Macroautophagy/autophagy plays an important role against pathogen infection in mammals and plants. However, little has been known about the role of autophagy in the interactions of insect vectors with the plant viruses, which they transmit. Begomoviruses are a group of single-stranded DNA viruses and are exclusively transmitted by the whitefly Bemisia tabaci in a circulative manner. In this study, we found that the infection of a begomovirus, tomato yellow leaf curl virus (TYLCV) could activate the autophagy pathway in the Middle East Asia Minor 1 (MEAM1) species of the B. tabaci complex as evidenced by the formation of autophagosomes and ATG8-II. Interestingly, the activation of autophagy led to the subsequent degradation of TYLCV coat protein (CP) and genomic DNA. While feeding the whitefly with 2 autophagy inhibitors (3-methyladenine and bafilomycin A1 ) and silencing the expression of Atg3 and Atg9 increased the viral load; autophagy activation via feeding of rapamycin notably decreased the amount of viral CP and DNA in the whitefly. Furthermore, we found that activation of whitefly autophagy could inhibit the efficiency of virus transmission; whereas inhibiting autophagy facilitated virus transmission. Taken together, these results indicate that TYLCV infection can activate the whitefly autophagy pathway, which leads to the subsequent degradation of virus. Furthermore, our report proves that an insect vector uses autophagy as an intrinsic antiviral program to repress the infection of a circulative-transmitted plant virus. Our data also demonstrate that TYLCV may replicate and trigger complex interactions with the insect vector.